بين النقد الثقافي والأدب التفاعلي: مقاربة فكرية - طالبي, عبد القادر (جامعة الوادي - University of Eloued, 2020)
ملخص: لم يعد الأدب التفاعلي هواية يفضلها بعض المراهقين من جيل الفضاء الأزرق والهواتف الذكية ،بل صار جنسا أدبيا يرغمنا على احترامه،لأن نصوصه الرقمية غزت شبكة الانترنت ومواقع التواصل الاجتماعي ،و عوضت صفحات الكتب وقاعات المكتبات،التي تحولت إلى مساحات مغبرة ،تنبعث منها رائحة الخراب.هذه الأنماط الجديدة من النصوص الأدبية تحولت إلى مادة أدبية ومعرفية مستهلكة لدى المثقف المعاصر الذي أصبح رصيده الثقافي يعتمد بشكل كبير على مواد رقمية يتزايد استهلاكه لها يوما بعد يوم ،لدرجة يمكننا أن نعطيه صفة المثقف الرقمي. و انطلاقا من هذه الفكرة جاء هذا البحث محاولا الوصول بالقارئ إلى فهم العلاقة بين النقد الثقافي والأدب التفاعلي من خلال رؤية علمية مبنية على االمقاربة الفكرية في مفهوم النقد الثقافي وصلته بالأدب التفاعلي والنص الأدبي الجديد. Abstract Interactive Literature is no longer a hobby favored by some teenagers from the generation of blue space and smart phone, but has become a genre forcing us to respect, because digital texts invaded the Internet and social networking sites, which replaced the pages of books and library halls, which turned on dusty spaces, emitting a smell of ruin These new types of literary texts have been transformed into literary and cognitive material consumed by the contemporary intellectual, whose cultural balance has become so dependent on digital materials that are increasingly consumed by them, that we can give him the status of a digital intellectual. Based on this idea, this research attempted to reach the reader to understand the relation between cultural criticism and interactive literature through a scientific vision based on the intellectual approach in the concept of cultural criticism and its relationship to interactive literature and new literary text.. Keywords: cultural criticism, intellectual, Interactive Literature, globalization, new text.
مقال
Keywords: النقد الثقافي،المثقف،الأدب التفاعلي،العولمة، النص الجديد